Low-Temperature Sulfidic-Ice Microbial Communities, Borup Fiord Pass, Canadian High Arctic - Trivedi, Christopher B.; Lau, Graham E.; Grasby, Stephen E.; Templeton, Alexis S.; Spear, John R. (Frontiers in Microbiology, 2018)
A sulfur-dominated supraglacial spring system found at Borup Fiord Pass (BFP), Ellesmere Island, Nunavut, Canada, is a unique sulfur-on-ice system expressed along the toe of a glacier. BFP has an intermittent flowing, subsurface-derived, glacial spring that creates a large white-yellow icing (aufeis) that extends down-valley. Over field campaigns in 2014, 2016, and 2017, numerous samples were collected and analyzed for both microbial community composition and aqueous geochemistry. Samples were collected from multiple site types: spring discharge fluid, aufeis (spring-derived ice), melt pools with sedimented cryoconite material, and mineral precipitate scrapings, to probe how microbial communities differed between site types in a dynamic freeze/thaw sulfur-rich system. Dissolved sulfate varied between 0.07 and 11.6 mM and was correlated with chloride concentrations, where the fluids were saltiest among spring fluids. The highest sulfate samples exhibited high dissolved sulfide values between 0.22 and 2.25 mM. 16S rRNA gene sequencing from melt pool and aufeis samples from the 2014 campaign were highly abundant in operational taxonomic units (OTUs) closely related to sulfur-oxidizing microorganisms (SOM; Sulfurimonas, Sulfurovum, and Sulfuricurvum). Subsequent sampling 2 weeks later had fewer SOMs and showed an increased abundance of the genus Flavobacterium. Desulfocapsa, an organism that specializes in the disproportionation of inorganic sulfur compounds was also found. Samples from 2016 and 2017 revealed that microorganisms present were highly similar in community composition to 2014 samples, primarily echoed by the continued presence of Flavobacterium sp. Results suggest that while there may be acute events where sulfur cycling organisms dominate, a basal community structure appears to dominate over time and site type. These results further enhance our knowledge of low-temperature sulfur systems on Earth, and help to guide the search for potential life on extraterrestrial worlds, such as Europa, where similar low-temperature sulfur-rich conditions may exist.